2008
DOI: 10.1016/j.brainres.2008.06.048
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of P300 amplitude on gamma synchrony breaks down in schizophrenia

Abstract: Introduction-Auditory P300 amplitude reduction in schizophrenia is canonical and may be explained by poor synchronization or reduced power of the underlying neural activity. We asked if patients have reduced synchrony and power, and whether together with P300 amplitude, they make unique or overlapping contributions to the discrimination between patients and controls. We also asked whether people who have large P300s have higher power and greater synchrony of neural activity, and if the relationships between P3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 31 publications
4
61
3
Order By: Relevance
“…Of special note, ketamine attenuates the depression in late induced theta power, leaving only a short depressed activity after the second click located in the high theta frequency range. This may correlate with recent human EEG data showing a decrease in the 8-12 Hz total power during a P300 task in the control healthy group and an attenuation of this decrease in patients with schizophrenia (Ford, Roach, Hoffman, & Mathalon, 2008). Because ketamine is thought to exert its effects via blocking NMDA receptors, these data support their role in mediating the balance between theta and gamma responses to sensory stimuli with implications for dysfunction in schizophrenia.…”
Section: Discussion Theta and Gamma Oscillationssupporting
confidence: 86%
“…Of special note, ketamine attenuates the depression in late induced theta power, leaving only a short depressed activity after the second click located in the high theta frequency range. This may correlate with recent human EEG data showing a decrease in the 8-12 Hz total power during a P300 task in the control healthy group and an attenuation of this decrease in patients with schizophrenia (Ford, Roach, Hoffman, & Mathalon, 2008). Because ketamine is thought to exert its effects via blocking NMDA receptors, these data support their role in mediating the balance between theta and gamma responses to sensory stimuli with implications for dysfunction in schizophrenia.…”
Section: Discussion Theta and Gamma Oscillationssupporting
confidence: 86%
“…These mostly concern the consistency of findings regarding the gamma band and the lack of contribution of slow frequencies for P300 reported by Ford et al (2008). Given the high dependency of the P300 on the synchrony and power of delta band activity, and the consistent reports of reduced slow frequency activity in patients with schizophrenia, a relation between P300 and delta activity would be expected for both control and patient samples.…”
Section: Introductionmentioning
confidence: 87%
“…Others (e.g., see Ergen et al, 2008) also reported a reduced visual P300 and evoked delta power, but not total delta power, which suggests that temporal jitter on the onset of the neural generators of the P300 component may result in less stimulus-locked delta activity. Ford et al (2008) have shown that the reduced P300 may be accounted by a reduction in power and ITC on the theta and gamma bands. They have reported that the amplitude of the P300 displays a dependence on the synchrony of the gamma band activity in controls, and that this dependency is absent in patients.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies related to brain pathological states indicate that the amplitude of event-related delta oscillations decreases in Alzheimer's disease (Yener et al, 2008), mild cognitive impairment (Kurt et al, 2014;Yener et al, 2013), schizophrenia (Ergen et al, 2008;Ford et al, 2008), bipolar disorder (Atagün et al, 2014) and alcoholism (Kamarajan et al, 2004). However, there are few studies in the literature investigating delta ERO in healthy elderly (Schmiedt-Fehr and .…”
Section: Introductionmentioning
confidence: 95%